KLASYFIKACJA I KATEGORYZACJA W SYSTEMIE OCHRONY ZABYTKÓW - Boguslaw Szmygin (Ochrona Dziedzictwa Kulturowego)
Contemporarily, historic monuments and sites are highly diverse and vast in number. This means that each asset and property has different value and, hence, different principles and forms of historic preservation need to be applied. Diversification of historic monuments and sites should be a part of the monument protection system and based on the widely accepted and followed methodology. No single methodology allowing for assessing the value of all historic monuments and sites has been developed yet. For this reason, diversification of historic monuments and sites is not applied in the international doctrinal documents. The most comprehensive method of assesing heritage value has been implemented into UNESCO’s World Heritage system. It consists on comparing assets within a certain reference group, yet it does not involve value gradation. Within the monument protection system, historic monuments and sites can be divided into two major groups, i.e. classes (in terms of the value of an asset or property) and categories (in terms of the specific features of an asset or property). In the Polish system of historic monuments and sites, application of categorisation (typology-based groups) is justified. However, for practical reasons (a risk of protection being depreciated and weakened), classes can be applied in limited scope (valuing groups).